HUMAN RIGHTS IN KAZAKHSTAN AND THE UNITED KINGDOM: (Farabi Journal of Social Sciences, 2020)
The article examines the human rights issues based on the experience of the Republic of Kazakhstanand the United Kingdom. A comparative analysis of the scientific views of domestic and foreign scientists; reveals theproblematic aspects of protecting human rights.In the era of globalization, the role of the human rights in solving urgent problems of human civilization is growing.In recent years, dramatic changes have occurred in the global legal system and the legal system of Kazakhstan. Thesechanges will serve as the basis for the protection, enforcement and development of human rights. On the one hand, itis a process of integration and regionalization based on world globalization, on the other hand, domestic political andliberal reform processes in Kazakhstan.The main aim of the articles in the context of globalization, to do a comparative analysis of human rights in theRepublic of Kazakhstan and in the UK, to develop further recommendations for improving the human rights legislationof the Republic of Kazakhstan.